Treatment interventions to maintain abstinence from alcohol in primary care: systematic review and network meta-analysis - Cheng, Hung-Yuan; McGuinness, Luke A; Elbers, Roy G; MacArthur, Georgina J; Taylor, Abigail; McAleenan, Alexandra; Dawson, Sarah; López-López, José A; Higgins, Julian P T; Cowlishaw, Sean; Lingford-Hughes, Anne; Hickman, Matthew; et al. (BMJ (Online), 2020)
AbstractObjectiveTo determine the most effective interventions in recently detoxified, alcohol dependent patients for implementation in primary care.DesignSystematic review and network meta-analysis.Data sourcesMedline, Embase, PsycINFO, Cochrane CENTRAL, ClinicalTrials.gov, and the World Health Organization’s International Clinical Trials Registry Platform.Study selectionRandomised controlled trials comparing two or more interventions that could be used in primary care. The population was patients with alcohol dependency diagnosed by standardised clinical tools and who became detoxified within four weeks.Data extractionOutcomes of interest were continuous abstinence from alcohol (effectiveness) and all cause dropouts (as a proxy for acceptability) at least 12 weeks after start of intervention.Results64 trials (43 interventions) were included. The median probability of abstinence across placebo arms was 25%. Compared with placebo, the only intervention associated with increased probability of abstinence and moderate certainty evidence was acamprosate (odds ratio 1.86, 95% confidence interval 1.49 to 2.33, corresponding to an absolute probability of 38%). Of the 62 included trials that reported all cause dropouts, interventions associated with a reduced number of dropouts compared with placebo (probability 50%) and moderate certainty of evidence were acamprosate (0.73, 0.62 to 0.86; 42%), naltrexone (0.70, 0.50 to 0.98; 41%), and acamprosate-naltrexone (0.30, 0.13 to 0.67; 17%). Acamprosate was the only intervention associated with moderate confidence in the evidence of effectiveness and acceptability up to 12 months. It is uncertain whether other interventions can help maintain abstinence and reduce dropouts because of low confidence in the evidence.ConclusionsEvidence is lacking for benefit from interventions that could be implemented in primary care settings for alcohol abstinence, other than for acamprosate. More evidence from high quality randomised controlled trials is needed, as are strategies using combined interventions (combinations of drug interventions or drug and psychosocial interventions) to improve treatment of alcohol dependency in primary care.Systematic review registrationPROSPERO CRD42016049779.